Quality Culture in the Development of Islamic Religious Education: Concepts, Implementation, and Impact - Tresna Nuryana; Siti Julaiha (Bulletin of Pedagogical Research, 2025)
In the era of globalization, Islamic educational institutions face significant challenges in balancing academic competence with the development of religious character. Islamic Religious Education (PAI) serves not only as a vehicle for knowledge transmission but also for the internalization of moral and spiritual values. This study aims to analyze the concept of quality culture from an Islamic educational perspective, explore its implementation strategies in PAI instruction, and examine its impact on the broader educational ecosystem. Using a qualitative library research approach, this study reviews literature on integrated quality management and Islamic educational principles. The findings reveal that a quality culture in PAI is grounded in the principles of ihsan (excellence in character) and anti-corruption values. Its implementation involves adaptive curriculum design, technology-based learning innovations that maintain valuable traditions (al-muḥāfazhah ‘ala al-qadīm al-ṣāliḥ), and the role of teachers as uswah ḥasanah (exemplary models). Establishing a quality culture fosters a religiously oriented academic environment, strengthens teacher professionalism, and cultivates students who embody both intellectual capability and spiritual integrity. The synergy between schools, families, and communities emerges as a critical factor in sustaining an effective quality culture.